Meningkatkan Keterampilan Komunikasi, Sikap Kerja Sama dan Penguasaan Konsep Siswa Melalui Implementasi Pembelajaran Inkuiri [Enhancing Communication Skill, Teamwork, and Student’s Mastery Concept Through the Implementation of Inquiry Learning] - Ita Minar Oktavia Pardosi (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2021)
Communication skills, cooperative attitude and mastery of concepts are very important for students to have. This research aims to know the increasing of communication skills, teamwork and student's mastery concept through inquiry learning model. This research was carried out using a quantitative approach through the experimental method of one group pre-test post-test. Data were obtained through 34 students in one class. The results showed that there were differences in communication skills, cooperative attitudes and mastery of students' concepts from before and after the implementation of inquiry learning, which was known from the increase in average scores and N-gain.